Modern Cryptography Current Challenges and Solutions - Domb, Menachem (IntechOpen, 2019)
Cyber security is taking on an important role in information systems and data transmission over public networks. This is due to the widespread use of the Internet for business and social purposes. This increase in use encourages data capturing for malicious purposes. To counteract this, many solutions have been proposed and introduced during the past 80 years, but Cryptography is the most effective tool. Some other tools incorporate complicated and long arithmetic calculations, vast resources consumption, and long execution time, resulting in it becoming less effective in handling high data volumes, large bandwidth, and fast transmission. Adding to it the availability of quantum computing, cryptography seems to lose its importance. To restate the effectiveness of cryptography, researchers have proposed improvements. This book discusses and examines several such improvements and solutions.